Higher order color mechanisms : Evidence from noise-masking experiments in cone contrast space - Hansen, Thorsten; Gegenfurtner, Karl R.; Justus Liebig University Giessen (My University, 2013)
This study addresses a fundamental question concerning the number of cortical, i.e., higher order mechanisms in color vision. The initial subcortical stages in color vision can be described by three cone mechanisms, S, M, L, and three pairs of second-stage mechanisms (achromatic L + M and -L - M, chromatic S - (L + M) and -S + (L + M), and chromatic L - M and M - L). The further mechanistic description of cortical color vision is controversial. On the one hand, numerous studies that defined their stimuli in a color-opponent Derrington-Krauskopf-Lennie (DKL) color space found evidence for higher order mechanisms. On the other hand, some studies that defined their stimuli in cone contrast (CC) space failed to find such evidence. Here we show that this failure was due to a restricted choice of stimuli. We used a noise-masking paradigm to measure discrimination thresholds for textured patterns modulated along chromatic directions in CC space. Unlike previous studies we defined noise directions in DKL space and converted them to CC space. When the noise contrast was sufficiently high we found selective masking, but this did not occur when the noise contrast was low. Selective masking indicates higher order mechanisms, since so far no alternative model has been proposed. Previous studies in CC space failed to find selective masking due to the low contrast of the noise and due to the restricted choice of perceptually highly similar noise directions that mainly stimulated the second-stage mechanisms. We conclude that cortical color vision is governed by higher order mechanisms.
Keywords: color vision; higher order color mechanisms; noise masking; ddc:150